Remodeling of immune system functions by extracellular vesicles - Neyrinck-Leglantier, Deborah; Tamagne, Marie; Ben Rayana, Raida; Many, Souganya; Pinheiro, Marion Klea; Delorme, Adèle Silane; Andrieu, Muriel; Boilard, Eric; Cognasse, Fabrice; Hamzeh-Cognasse, Hind; Perez-Patrigeon, Santiago; Lelievre, Jean-Daniel; et al. (Frontiers in Immunology, 2025)
IntroductionThe treatment of chronic viral infections can often bring viral replication under control. However, chronic immune activation persists and can lead to the development of comorbid conditions, such as cardiovascular disease and cancer. This is particularly true for people living with HIV (PLWH), who have significantly more extracellular vesicles from membrane budding, also called plasma microparticles (MPs), than healthy individuals (HDs), and a much more immunomodulatory phenotype. We hypothesized that the number and phenotypic heterogeneity of MPs can trigger a functional remodeling of immune responses in PLWH, preventing full immune restoration.MethodsWe investigated the rapid impact of three types of MPs — derived from membrane budding in platelets (CD41a+ PMPs), monocytes (CD14+ MMPs) and lymphocytes (CD3+ LMPs) in the plasma of PLWH or HDs—on four cell types (CD4+ and CD8+T lymphocytes, monocytes and DCs).ResultsThese investigations of the short multiple interactions and functions of MPs with these cells revealed an increase in the secretion of cytokines such as IFNg, IL2, IL6, IL12, IL17 and TNFa by the immune cells studied following interactions with MPs. We show that this functional remodeling of immune cells depends not only on the number, but also on the phenotype of MPs.ConclusionThese data suggest that the large numbers of MPs and their impact on functional remodeling in PLWH may be incompatible with the effective control of chronic infections, potentially leading to chronic immune activation and the onset of comorbid diseases.